Properties of solution for the game of one attacker against several defenders - Vrublevskaja, I. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Н. Врублевская. Свойства решения игры одного нападающего против нескольких защитников I. Vrublevskaja. Vieno puolėjo prieš keletą gynėjų lošimo sprendinio savybės